2017
DOI: 10.1101/181792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic changes in clonal architecture during disease progression in follicular lymphoma

Abstract: Follicular lymphoma (FL) is typically a slow growing cancer that can be effectively treated. Some patients undergo transformation to diffuse large B cell lymphoma (DLBCL), which is frequently resistant to chemotherapy and is generally fatal. Targeted sequencing of DNA and RNA was applied to identify mutations and transcriptional changes that accompanied transformation in a cohort of 16 patients, including 14 with paired samples. In most cases we found mutations that were specific to the FL clone dominant at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…SuperFreq was designed to detect and track somatic mutations in exomes, and it has been applied to study breast cancer metastasis [2,21], lung cancer xenografts [22], gastric cancer organoids [23], and myeloid leukaemia [24]. SuperFreq is highly versatile and it has since been applied to study small capture sets [25] and low pass whole genomes [26]. We want to draw attention to De Mattos-Arruda [21], where multiple pipelines, including SuperFreq, were used in parallel for clonal tracking, and the authors found overall quite consistent results between methods, providing an independent example of how SuperFreq can be applied for an end-toend analysis on real data.…”
Section: Discussionmentioning
confidence: 99%
“…SuperFreq was designed to detect and track somatic mutations in exomes, and it has been applied to study breast cancer metastasis [2,21], lung cancer xenografts [22], gastric cancer organoids [23], and myeloid leukaemia [24]. SuperFreq is highly versatile and it has since been applied to study small capture sets [25] and low pass whole genomes [26]. We want to draw attention to De Mattos-Arruda [21], where multiple pipelines, including SuperFreq, were used in parallel for clonal tracking, and the authors found overall quite consistent results between methods, providing an independent example of how SuperFreq can be applied for an end-toend analysis on real data.…”
Section: Discussionmentioning
confidence: 99%
“…SuperFreq was designed to detect and track somatic mutations in exomes, and it has been applied to study breast cancer metastasis [2,21], lung cancer xenografts [22], gastric cancer organoids [23], and myeloid leukaemia [24]. SuperFreq is highly versatile and it has since been applied to study small capture sets [25] and low pass whole genomes [26]. We want to draw attention to De Mattos-Arruda [21], where multiple pipelines, including SuperFreq, were used in parallel for clonal tracking, and the authors found overall quite consistent results between methods, providing an independent example of how SuperFreq can be applied for an end-to-end analysis on real data.…”
Section: Discussionmentioning
confidence: 99%